MALAY TRADITIONAL FERMENTED FOOD: WILL MILLENNIALS EAT IT? - Norfezah Md Nor; Anis Syafiqah Kamaruddin (Journal of Islamic, Social, Economics and Development, 2021)
Globalization and modernization are dynamic factors that influenced the millennialsto consume Malay traditional fermented food. Thus, this may lead to the challenge in creatingawareness towards sustainability of Malay traditional fermented food and avoid the possibilityof losing the value of food heritage among millennials. In addressing this issue, this study wasconducted to examine the behavioral intention in consuming the Malay traditional fermentedfood among millennials. An extended Theory of Planned Behavior (TPB) with modification wasemployed in this study. A quantitative e-survey was conducted through google form platform.The collected data of 131 millennial respondents were then analyzed with a descriptive statisticfollowed by correlation and multi regression using SPSS 21 version. The result showed allfactors including attitude (r=0.542, p=0.00), subjective norm (r=0.585, p=0.00), perceivebehavior control (r=0.40, p=0.651) and neophobia (r=0.214, p=0.014) have a positivesignificant relationship towards intention to consume Malay traditional fermented food amongmillennials. However, the multiple regression result revealed only three predictors explained37.0% of the variance (R2=0.383, F (3,127) =26.308, p<0.0005), which indicate 63% factorsthat influence the millennials behavioral towards the intention to consume Malay traditionalfermented food were also contributed by others factors. These results are expected to highlightthe significance of millennials generation’s role as an agent in continuing towards sustainingthe Malay traditional fermented food against the globalization and modernization. Hence, thismay have a positive impact on the traditional food business and tourism food heritage industrysustainability.